Palliative Radiofrequency Ablation Accelerates the Residual Tumor Progression Through Increasing Tumor-Infiltrating MDSCs and Reducing T-Cell-Mediated Anti-Tumor Immune Responses in Animal Model - Wu, Hao; Li, Su-shu; Zhou, Meijun; Jiang, An-Na; He, Yanni; Wang, Song; Yang, Wei; Liu, Hongmei (Frontiers in Oncology, 2020)
Previous studies showed that radiofrequency ablation (RFA) has a favorable treatment efficacy for hepatocellular carcinoma (HCC) or colorectal liver metastases (CRLMs). Palliative RFA (pRFA) resulting from larger HCC or multiple CRLMs further accelerated the progression of potential residual tumor, yet its mechanism was still unknown. This study investigated the influence of myeloid-derived suppressor cells (MDSCs) on T-cell immune responses and tumor recurrence after pRFA. CT26 tumor models were used. The percentage of MDSCs in peripheral blood was analyzed by flow cytometry after pRFA. The level of Th1 and Th2 cytokines were measured by ELISA through different treatments (n = 4/group). The tumor-infiltrating MDSCs, dendritic cells, and intracellular cytokines level were analyzed by IHC staining after different treatments. The functional CD8+ T cells were confirmed by the co-localization immunofluorescence staining. The long-term outcomes were also evaluated through CT26 and 4T1 tumor models. The results showed that tumor models treated with pRFA displayed significant increases in the percentage of MDSCs of peripheral blood and tumor infiltration. The expression level of TGF-β and IL-6 after pRFA was higher than that before pRFA by ELISA and IHC staining. After depleting MDSCs by combining with Abs, the pRFA + Abs group achieved a higher level of Th1 cytokines and greatly enhanced the percentage of tumor-infiltrating functional CD8+ T cells when compared with pRFA alone. The depletion of MDSCs through combination with Abs also resulted in tumor regression. In conclusion, pRFA accelerates the residual tumor progression through increasing tumor-infiltrating MDSCs and reducing T-cell-mediated anti-tumor immune responses, which could provide a potential approach for delaying tumor recurrence caused by pRFA.